PSYCHONEUROLOGICAL ASPECTS OF JUVENILE RHEUMATOID ARTHRITIS - T.V. Podkletnova; L.M. Kuzenkova; E.I. Alexeeva ("Paediatrician" Publishers LLC, 2009)
This review describes basic aspects of neurological pathology in children with juvenile rheumatoid arthritis. Results of reviewed trials show that neurological and cognitive disorders, presenting in patients with juvenile rheumatoid arthritis, worsen patient's quality of life and need to be corrected with medicaments. Key words: children, juvenile rheumatoid arthritis, neurological patology. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):46-51)